Dynamic Mechanical Analysis of Bio-Based and Synthetic Petroleum Based Polymer Foams with Powder Type Organic Filler at Prolonged Ultra-Violet Exposure - M A, Zulhakimie; Mohd Rus, Anika Zafiah; Sulong, N S S; Mohd Zaini, Ahmad Shahrizan Shah; Mohd Salim, Nurul Syamimi (Emerging Advances in Integrated Technology, 2025)
Wood powder filler that have been added in the bio-based and epoxy polymer foams can be proved that it have ability to strengthen the structure of polymer foams. In this study, ‘Meranti’ type wood filler has been used as the filler. This study was developed to observe the pore size of each sample when expose to different hours of UV irradiation exposure using Optical Microscopy (OM). This study was also to compare the mechanical properties of every sample with different ratio filler of 0 wt%, 5 wt%, 10 wt%, 15wt% and 20 wt% at different hours of UV irradiation exposure which is 0 hour until 6,000 hours with increment of 2,000 hours. The testing was run by DMA Q800 TA machine. The samples that have 40 x 10 x 5 mm size were clamped in the machine to get the result of their mechanical properties. From the DMA testing, the results will show the value of tan delta, loss modulus and storage modulus. The value of tan delta shows that higher ratio filler will give the high value of tan delta. The epoxy polymer foams with powder filler have the highest value of tan delta compare to bio-based polymer foams. It proves that the higher filler ratio, the lower value of tan delta can be recorded. The result of storage and loss modulus was found to increase as the more filler ratio filler in the polymer foams. The higher the loss modulus and storage modulus, the lower the temperature. Bio-based polymer foams with high powder filler ratio can dissipate more energy as energy are lost as heat during UV irradiation exposure.